2015
DOI: 10.1245/s10434-015-4424-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Diagnostic Accuracy of Magnetic Resonance Imaging with Sonography in the Prediction of Breast Cancer Tumor Size: A Concordance Analysis with Histopathologically Determined Tumor Size

Abstract: MRI tends to overestimate the actual tumor size, while sonography frequently underestimates it. Combined sonography and MRI increases the accuracy of tumor size prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…MGM also overestimated in approximately 20% of patients. Other studies have also shown similar underestimation/overestimation rates for MGM and U/S . These findings underscore the deficiencies of breast imaging in delineating tumor size.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…MGM also overestimated in approximately 20% of patients. Other studies have also shown similar underestimation/overestimation rates for MGM and U/S . These findings underscore the deficiencies of breast imaging in delineating tumor size.…”
Section: Discussionsupporting
confidence: 71%
“…This method does not allow for accurate concordance because a measurement of >0.5 cm for a larger tumor does not have as much impact as for a smaller tumor. Another recent study by Lai et al used 25% of the maximal tumor size and found a better concordance rate for MRI and tumor size . We used 33% of the maximal tumor size, which allowed for higher concordance rates then a 25% cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…[8,11] Nipple inversion or retraction was evaluated using axial T1-weighted and fat-suppressed T2-weighted images. A complete loss of the normal nipple tip was considered as nipple inversion.…”
Section: Methodsmentioning
confidence: 99%
“…Table 4 summarizes the performance of different imaging studies in estimating tumour size. The tendency to overestimate lesion size by breast MRI was found by several authors [6, 10, 25, 26] and in more than 50% of the cohort of 682 patients of Lai et al [26]. This is partly related to the method of measurement of tumour size and the concordance thresholds established prior to examination.…”
Section: Discussionmentioning
confidence: 93%